Dibenzotetraaza[14]annulenes: versatile ligands for transition and main group metal chemistry - Mountford, P (1998)
This article presents an overview of the chemistry of metal complexes of dibenzotetraaza[14]annulene ligands and highlights most of the recent developments. The title tetraazamacrocycles are related to the porphyrins but have a smaller N4 coordination cavity 'hole size' and typically possess a non-planar, saddle-shaped conformation. The similarity of the dibenzotetraaza[14]annulenes to the porphyrins means that these synthetic macrocycles are of bioinorganic relevance, while their distinctive individual characteristics make them interesting ligands in their own right. In early transition metal chemistry, for example, the dibenzotetraaza[14]annulenes have been studied as potential alternatives to the ubiquitous bis(η-cyclopentadienyl) ligand set, while later transition metal derivatives can mimic certain biological systems and act as precursors to electroactive polymeric films. The dibenzotetraaza[14]annulenes have also recently allowed advances in structural and reactivity studies of main group organometallic and coordination compounds, including the stabilisation of new metal-chalcogenide multiple bonds.